Malpositioned nephrostomy tube with associated hemorrhagic pleural effusion. (2023) - Jaber, Johnny F.; Rosier, Luderve; Sykes, John J.; Asharaf, Afsana; Trillo, Cesar; Austin, Adam
Abstract: Pleural effusion of extra-vascular origin has a large differential diagnosis. Ultrasonography can be utilized alongside pleural fluid analysis to determine a pleural effusion's complexity and size, thus helping aid in both diagnostic and therapeutic management. We describe the case of a 38-year-old male with a prior medical history of neurogenic bladder and nephrolithiasis with percutaneous nephrostomy tube placed one week prior to presentation. Using ultrasonography, the nephrostomy tube was determined to be positioned within the pleural cavity with a resultant hemorrhagic pleural effusion.